2018
DOI: 10.1126/science.aah3648
|View full text |Cite
|
Sign up to set email alerts
|

Patients with familial adenomatous polyposis harbor colonic biofilms containing tumorigenic bacteria

Abstract: Individuals with sporadic colorectal cancer (CRC) frequently harbor abnormalities in the composition of the gut microbiome; however, the microbiota associated with precancerous lesions in hereditary CRC remains largely unknown. We studied colonic mucosa of patients with familial adenomatous polyposis (FAP), who develop benign precursor lesions (polyps) early in life. We identified patchy bacterial biofilms composed predominately of Escherichia coli and Bacteroides fragilis. Genes for colibactin (clbB) and Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
802
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(823 citation statements)
references
References 15 publications
18
802
2
1
Order By: Relevance
“…Infection with pks + E. coli induces anaphase bridging, chromosome aberrations, aneuploidy, and tetraploidy . Mucus degradation enables an increase in pks + E. coli adhesion, triggering increased DNA damage in colonic epithelial cells by colibactin . Bacteria‐host cell contact is required for the genotoxic effect of pks; therefore, an environment where bacteria can more readily take root in the epithelial layer could deliver more of the pks product colibactin to host cells in the epithelium .…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 99%
“…Infection with pks + E. coli induces anaphase bridging, chromosome aberrations, aneuploidy, and tetraploidy . Mucus degradation enables an increase in pks + E. coli adhesion, triggering increased DNA damage in colonic epithelial cells by colibactin . Bacteria‐host cell contact is required for the genotoxic effect of pks; therefore, an environment where bacteria can more readily take root in the epithelial layer could deliver more of the pks product colibactin to host cells in the epithelium .…”
Section: Typical Microbial Families Contributing To Colorectal Cancermentioning
confidence: 99%
“…57 In the colon, adherent bacteria such as Bacteroides fragilis are thought to promote adenomas and cancers as they produce enterotoxins that have tumorigenic effects including effects on signaling, cell adhesion molecules and cytokine alterations. 58, 59 Consistent with their role in modulating the immune response, gut bacterial profiles are recognized as influencing the immune response directed towards tumors. 15, 60 Several studies have shown that gut microbiome profiles influence the immune therapy response to checkpoint inhibitor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elevation of the iNos‐mediated nitrate respiration pathway provides a growth advantage to E. coli in the inflamed intestine of DSS‐treated C57BL/6 mice . Furthermore, the population of pks+ E. coli in the colonic biofilms of patients with familial adenomatous polyposis and Apc MinΔ716/+ mice is enriched by concurrent colonization of Bacteroides fragilis . In the current study, H. hepaticus infection increased levels of fecal pks+ E. coli , presumably due to inflamed large bowel of H. hepaticus ‐infected RagIl10gpt mice.…”
Section: Discussionmentioning
confidence: 99%